Evaluación del comportamiento hidrodinámico y de la operación del biorreactor anaerobio híbrido (2020)
In the present work, the objective was to evaluate the hydrodynamic behavior and the operation of an anaerobic hybrid bioreactor in which the ASTBR and REM configurations are combined, with the development of this technology it was possible to determine the behavior of the fluid inside the bioreactor by Hence its behavior, it was verified what the influence of materials such as the structured bed and the granular mud within it was going to be, to finally carry out the characterization of the biomass. To start, made synthetic waste water with a DQO of 4000 mg/L, having an artificial inoculum the granular mud coming of the Postobón sewage treatment power plant, it has develop in a stepped structured litter reactor, continue with an anaerobic digestion process when it was establishing some operation parameters as a hydraulic retention time minimum 36 hours, in this project it was getting the experimental hydraulic retention time and the theorist hydraulic retention time with values of 41,7 hours and 37,02 hours respectively, a temperature of 35°C, a pH between 6,5 and 7,5 and a flow rate of 6,171 mL/min. Later, it was making adsorption tests of granular mud structured litter with a tracer of green color, with the final purpose decide if the influence of these affected or not the hydrodynamic behavior of the fluid inside of the bioreactor.